2018
DOI: 10.2147/cia.s157523
|View full text |Cite
|
Sign up to set email alerts
|

The good, the bad, and the ugly of calcium supplementation: a review of calcium intake on human health

Abstract: Calcium is an important integrative component of the human body and critical for human health. It has been well established that calcium intake is helpful in the prevention and treatment of osteoporosis, which has become one of the most serious public health problems across the world. However, community-dwelling adults with and without osteoporosis are rarely concerned or even not aware of the potential side effects of high or inappropriate doses of calcium intake. Some recent studies have revealed that excess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(82 citation statements)
references
References 69 publications
0
74
0
8
Order By: Relevance
“…sodium and calcium containing medications also increases the risk of developing kidney stones crystal urea is also risk factor as well as having a family history [10] [11]. These risk factors will lead to a number of things first some of these risk factors will increase urinary solute concentration including concentration of calcium, uric acid, and calcium oxalate and sodium [12]. Hypertension, obesity [13] and gout all can lead to renal stones.…”
Section: Discussionmentioning
confidence: 99%
“…sodium and calcium containing medications also increases the risk of developing kidney stones crystal urea is also risk factor as well as having a family history [10] [11]. These risk factors will lead to a number of things first some of these risk factors will increase urinary solute concentration including concentration of calcium, uric acid, and calcium oxalate and sodium [12]. Hypertension, obesity [13] and gout all can lead to renal stones.…”
Section: Discussionmentioning
confidence: 99%
“…For the latter, Vernia et al (19) have indicated that inadequate calcium intake is present in IBD patients and that this represents a reversible risk factor given that diets in these patients contained significantly less calcium than healthy controls. The context that calcium and vitamin D supplementation disparities can be benchmarked on gender, age, race/ethnicities, dietary preferences, and household economics has been widely advocated (20,21), but the review of Wallace et al (20) pointed out that "low-income, overweight and/or obese minority population may be at greater risk of calcium and vitamin D insufficiency." While Reid et al (22) made a case that calcium supplements may have very little role to play in the prevention or treatment of osteoporosis, this editorial view is that cardiovascular integrity and heart health is of utmost and paramount importance.…”
Section: Editorialmentioning
confidence: 99%
“…Calcium is the most abundant stored nutrient in the human body, and is involved in several physiological processes, such as bone development, vascular contraction, vasodilation, muscle functions, nerve transmission, intracellular signaling, and hormonal secretion 1,2 . Calcium homeostasis, which refers to the maintenance of a serum calcium concentration between 8.5 and 10.5 mg/dL (2.1 to 2.6 mmol/L), is controlled by the parathyroid hormone, calcitriol and calcitonin 3,4 . Perturbations of calcium homeostasis can be life‐threatening, with hypercalcemia resulting in lethargy, kidney stones, constipation, loss of appetite and confusion, and hypocalcemia resulting in osteoporosis, seizures and arythmias 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Recommendations for daily calcium intake have been issued by governmental and non‐governmental organizations in several countries 1,4 . Adequate calcium intakes currently vary from 500 to 1200 mg/day in adults, depending on age and gender 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation